Elucidation of partial activation of cannabinoid receptor type 2 and identification of potential partial agonists: Molecular dynamics simulation and structure-based virtual screening. (August 2022) - Uba, Abdullahi Ibrahim; Aluwala, Harika; Liu, Haiguang; Wu, Chun
Abstract: Cannabinoid receptor type 2 (CB2R) is a member of the class A G protein-coupled receptor (GPCRs) family and a component of the endocannabinoid system that is modulated by the psychoactive chemical from Cannabis sativa, partial agonist Δ 9 -tetrahydrocannabinol (Δ 9 -THC). Selective activation of CB2R allows for the treatment of inflammatory and immune-related conditions without the psychotropic effects of CB1R. While CB2R-selective agonists are available, CB2R partial agonists are scarce. Hence, the pharmacological difference between CB2R full agonists and partial agonists remains to be deciphered, prompting the search for novel partial agonists. Here, using an induced-fit docking approach, we built a partial agonist Δ 9 -THC bound CB2R system from the inactive CB2R structure (PDB ID: 5ZTY) and performed microsecond molecular dynamics (MD) simulations. The simulations reveal an upward shift of the "toggle switch" W6.48 (258) and minor outward movement of the transmembrane helix 6 (TM6). Dynamic network model identifies a possible communication path between the ligand and the toggle switch" W6.48 (258) . Furthermore, to identify potential CB2R partial agonists, we conducted structure-based virtual screening of ZINC15 "Druglike" library containing 17, 900742 compounds against 3 conformations derived from MD simulation of CB2R complexed with partial agonist Δ 9 -THC using Glide virtual screening protocol comprising various filters with increasing accuracy. Nine diverse compounds predicted to have high MM-GBSA binding energy scores and good ADMET properties (including high gastrointestinal absorption and low toxicity) are proposed as potential CB2R partial agonists. Graphical Abstract: Elucidation of partial activation of cannabinoid receptor type 2 and identification of potential partial agonists: Molecular dynamics simulation and structure-based virtual screening. MD conformation of partial agonist bound CB2. Crystal structure of agonist bound CB2 (6KPC). ga1 Highlights: A partial agonist Δ 9 -THC bound CB2R system was built from the inactive CB2R structure (PDB ID: 5ZTY). A ZINC15 "druglike" library containing ∼17 million compounds was virtually screened for CB2R partial agonists. Based on MM-GBSA calculations and good ADMET filtering, nine compounds are proposed as potential CB2R partial agonists.